Argatroban in the management of heparin-induced thrombocytopenia: a multicenter clinical trial. Issue 1 (December 2015) - Tardy-Poncet, Brigitte; Nguyen, Philippe; Thiranos, Jean-Claude; Morange, Pierre-Emmanuel; Biron-Andréani, Christine; Gruel, Yves; Morel, Jérome; Wynckel, Alain; Grunebaum, Lelia; Villacorta-Torres, Judith; Grosjean, Sandrine; de Maistre, Emmanuel
Abstract Introduction The aim of this study was to collect data in France in patients with heparin-induced thrombocytopenia who required parenteral anticoagulation and for whom other non-heparin anticoagulant therapies were contraindicated including patients with renal failure, cross-reactivity to danaparoid or at high hemorrhagic risk. Methods A total of 20 patients, of mean age 72 ± 10 years, were enrolled in this open-label, multicenter clinical study. Exploratory statistical data analysis was performed with descriptive interpretation of intra-individual comparisons using simple univariate statistics. Results The diagnosis of HIT was confirmed in 16 subjects by an independent scientific committee. Fourteen patients (70 %) were in an intensive care unit during the course of the study. Patients were treated with argatroban for a mean duration of 8.5 ± 6.1 days. The mean starting dose of argatroban was 0.77 ± 0.45 μg/kg/min. Platelet recovery was rapid. aPTT and anti-IIa activity assays were used to monitor the dose of argatroban. The mean baseline aPTT value was 45.0 ± 9.8 sec and increased to 78.2 ± 35.8 sec two hours after initiating argatroban. At this time mean argatroban concentration was 0.34 ± 0.16 and 0.61 ± 0.28 μg/ml using ECT and TT measurements, respectively. New and/or extended thromboses were reported in 25 % of patients and major bleedings were documented in 15 %. Six patients died due to their underlying medical condition. Conclusion Considering its hepatic elimination and its short half-life, argatroban can be considered as a safe therapeutic option in HIT patients at high hemorrhagic risk and with renal failure, particularly in an ICU setting.